ROLE OF INFLAMMATION IN OBESITY RELATED METABOLIC DISORDERS. - DUGGIRALA RAJARAJESWARI (International Journal of Pharma and Bio Sciences, 2014)
Globally, obesity is a major contributor to the burden of several chronic metabolic diseases, including type 2 diabetes mellitus and cardiovascular diseases. With changing life style, obesity has now become a global phenomenon affecting all socioeconomic groups, irrespective of age, sex or ethnicity. Morbid obesity and co morbidities of metabolic syndrome, such as hypertension, dyslipidemia and glucose intolerance are now increasingly recognized in young adults predisposing them to early cardiovascular diseases. Obesity is now viewed as a low grade inflammatory disease, characterized by increased levels of inflammatory markers like C-reactive protein, TNF-α, interleukins and other adipokines that promote insulin resistance in liver and skeletal muscle ultimately leading to the clinical expression of various metabolic disorders. Because of the reversibility of obesity related diseases with suitable interventional strategies, it is important to identify and treat the pro inflammatory state of obesity to prevent premature deaths due to metabolic diseases. The relationship between obesity, inflammation and metabolic disorders was investigated extensively in several populations. This review aims at giving a general view on the role of inflammation in obesity related metabolic disorders and summarizing the recent progress. Elucidation of the mechanisms that link obesity with inflammation and metabolic disorders will not only contribute to the understanding of the patho physiology of obesity, but also open to novel strategies for prevention and treatment of pro-inflammatory state of obesity and obesity related metabolic disorders.